A numerical study on the effectiveness of cement grout improvement to Bangkok subsoils in avoiding the impact on piled foundations of adjacent structures from shield tunneling - Watchirawit Laopongcharoen; Chao, Kuo Chieh; Noppadol Phien-Wej; Avirut Puttiwongrak; Krit Saowiang; Royal Thai Government (RTG) (Pathum Thani, Thailand : Asian Institute of Technology, 2023)
This research investigates the effectiveness of various cement grout protection schemes employed to mitigate the impact of shield tunneling on pile foundations of adjacent structures in Bangkok subsoil conditions. A comprehensive analysis of case histories and previous research is conducted to categorize grout protection schemes into three main types: Grout Zone between Pile Foundation and Tunnel, Grout Zones for Pile Foundation, and Grout Zone at Tunnel. A detailed analysis is then performed to assess the efficiency of these schemes in different pile tip depth scenarios (shallow, medium, and deep), derived from the typical pile tip depths of buildings in Bangkok. Results reveal that grout zone application at the tunnel yields the most favorable outcomes for mitigating tunneling effects on adjacent pile foundations, particularly in shallow pile depth situations. This is primarily due to the fact that the critical zone of ground movement instigated by tunneling occurs around the tunnel surface, and enhancing soil properties in this essential region constitutes the most effective approach to curtail ground movement and safeguard adjacent pile foundations. Additionally, the analysis highlights the importance of changing the dimensions of the grout zone and their impact on the effectiveness of that grout protection scheme. Based on the findings, this research contributes valuable insights to the field of tunneling engineering and can help inform the selection of appropriate grout protection schemes in real-world projects to minimize the impact of shield tunneling on pile foundations of adjacent structures in Bangkok subsoil conditions.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Geotechnical and Earth Resources Engineering
Thesis (M. Eng.) - Asian Institute of Technology, 2023
Keywords: Cement grout -- Thailand -- Bangkok; Subsoils -- Thailand -- Bangkok; Finite element method -- Mathematics